(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
Watch Ruparanganda’s book, Genitals are Assets: Sexual and Reproductive Behaviours of Street Children of Harare, Zimbabwe, in the era of the HIV and Aids Pandemic, is extremely thought provoking and will make you want to laugh and cry at the same time. It explores the sexual and economic relations amongst the street children of Harare, Zimbabwe, in a language that is effortless and compelling. This is a book for both the deep academics and ordinary readers. Underneath everything else, this book goes into important theoretical and methodological debates about power differentials between men and women in society.